The impact of employees' values on role engagement: Assessing the moderating effects of distributive justice. Issue 8 (15th September 2017) - Rice, Bridget; Fieger, Peter; Rice, John; Martin, Nigel; Knox, Kathy
Abstract : Purpose: The purpose of this paper is to investigate the manner in which employees' experience of distributive justice (DJ) moderates the impact of intrinsic and extrinsic values on role engagement (RE). RE is especially important in the healthcare setting (examined here) due to the sector's complexity, changeability and emotionally challenging nature. Design/methodology/approach: Using data collected from a survey of employees from a large government health district in Southeast Queensland (Australia), this study examined the determinants of RE among a group of employees working across three hospital locations. Findings: The focus of the study was on the impact, both directly and in combination, of espoused extrinsic and intrinsic values and perceived DJ on RE. The authors identify strong direct effects from DJ on RE, and complex third-order effects for the combinations of intrinsic (IM) and extrinsic motivation and DJ in predicting RE. Research limitations/implications: As a cross-sectional and attitudinal survey, care must be taken in relation to common-method variance. Post hoc controls were performed in relation to this. Practical implications: DJ is important for all, and is a powerful motivator for engagement of employees reporting highly on IM. There is evidence that the most engaged employees are not those most motivated by extrinsic rewards alone, although employees who are motivated primarily by extrinsic rewards alone can be highly engaged when they experience high levels of DJ. Social implications: For managers seeking to engage their employees, an understanding of the different motivators for intrinsically vs extrinsically inclined employees is important. Taken together, these results suggest that employee RE is driven by a complex set of factors that differ between employees. Managing this complexity is an important consideration for managers. Originality/value: This is the first empirical study to show these interaction effects using these measures. The healthcare context, generally under researched, also features in this study.